Estimating Currents From Argo Trajectories in the Bothnian Sea, Baltic Sea - Roiha, Petra; Siiriä, Simo-Matti; Haavisto, Noora; Alenius, Pekka; Westerlund, Antti; Purokoski, Tero (Frontiers in Marine Science, 2018)
Argo floats have been used in the environmental monitoring of the Bothnian Sea, a sub-basin of the Baltic Sea, for five years as part of the Finnish Euro-Argo programme. The Bothnian Sea is considered to be an environmentally healthy part of the Baltic Sea because the deep waters of the basin are well-ventilated by inflowing oxygen-rich saltier and heavier surface layer waters of the Baltic Sea proper. Thus the deep water flow is of interest in the Bothnian Sea. In this study, we used Argo float data from six different long-term missions, from 111 to 512 days, to analyze the deep-water flow in the Bothnian Sea where no continuous monitoring of currents exist. We estimated mainly the flow below the expected halocline from the paths of the floats. We analyzed the movements statistically and estimated the error caused by the surface drift of the floats during their stay at the surface by using 3D hydrodynamic model results as reference data. Our results show a cyclonic resultant current in the deep trench of the Bothnian Sea. There seemed to be very little exchange between coastal zone and open-sea waters in deeper layers. The drifting speed of the floats in the deep layers of Bothnian Sea generally was around 2 cm/s but instantaneous speeds of tens of centimeters up to 30 cm/s in the middle-layer (50 dbars) were observed. In the Bothnian Sea deep, the deep trench on the Finnish side of the Bothnian Sea, the vast majority of the observations showed deep currents from south to north, with the same average speed of around 2 cm/s but the instantaneous maximum was smaller at 13 cm/s. Our study indicates that the routine Argo float observations can be used to get information on the deep currents in the basin in addition to traditional hydrographic observations. This helps in improving our understanding of the oxygen dynamics of the bottom layers of the Bothnian Sea, and the living conditions of the benthic phyto- and zooplankton communities there.